PERCEPTIONS OF WOMAN'S MENTAL HEALTH IN THE MAIN CHARACTER IN THE SHORT STORY THE YELLOW WALLPAPER - Karniasih, Ni Wayan Listia Dewi; Antari, Ni Made Suwari; Sukarini, Ni Wayan (Jurnal Review Pendidikan dan Pengajaran, 2024)
The aim of this study is to determine the mental health of the main character in a short story, who is often found to be suffering from postpartum depression. The research method used in this research is descriptive qualitative. This data was taken from the HCC Learning website. The data collection is carried out using the documentation method. The theory used in this research is Dobie's literary critical theory in the third edition of the book and Beauvoir's (1949) feminist theory. In the story The Yellow Wallpaper, the woman's perceived mental health is depicted as drastically declining due to confinement and lack of freedom, leading to isolation and delusions. The main character, who initially suffers from mild depression, becomes increasingly obsessed with the wallpaper pattern in her room, the ending in a complete mental collapse due to ineffective therapy and a stressful environment.